Impact of acute heat stress on hematological and biochemical profiles in Brown Swiss cows - Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; Mylostyvyi, Roman V.; Mylostyvy, R.; Mylostyvyi, R.; Milostivyi, R.; Милостивий, Роман Васильович (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv, 2025)
Heat stress (HS) is a critical environmental factor that disrupts dairy cows' physiological and metabolic balance, leading to impaired productivity, immune suppression, and oxidative stress. The Brown Swiss breed is known for its relatively higher thermotolerance, yet its hematological and biochemical responses to acute HS remain poorly understood. This study aimed to evaluate the impact of acute heat stress on the hematological and biochemical parameters of Brown Swiss dairy cows, identifying key physiological adaptations and potential biomarkers for stress assessment. The experiment involved 16 Brown Swiss cows in their second lactation, divided into a heat-stressed group (HYP, n = 8) and a control group (CON, n = 8). Heat stress conditions were characterized by a temperature-humidity index (THI) of 77.6 for five consecutive days. Hematological and biochemical analyses were conducted using an automated haematology analyzer and biochemical assays to assess oxygen transport capacity, metabolic adaptations, and immune responses. The results demonstrated significant changes in key blood parameters due to acute HS. Haemoglobin concentration decreased by 8.8% (P < 0.05), while platelet count and leukocyte levels were reduced by 30.2 % and 25.1 %, respectively (P < 0.05), indicating hematopoietic and immune alterations. Biochemical findings showed a 21.8 % increase in albumin concentration (P < 0.05), along with a 77.5 % rise in blood urea nitrogen (P < 0.05), suggesting enhanced protein catabolism. Additionally, total lipoprotein levels increased by 56.3 % (P < 0.05), and β-carotene concentration rose by 87.1 % (P < 0.05), reflecting metabolic shifts and oxidative stress adaptation. Thus, acute HS induces significant hematological and biochemical alterations in Brown Swiss cows, affecting oxygen transport, immune function, and metabolic regulation. The findings highlight the physiological trade-offs necessary for thermoregulation, emphasizing the need for targeted nutritional and environmental strategies to enhance heat stress resilience in dairy cattle. Further research is warranted to explore long-term adaptations and develop practical mitigation approaches. Тепловий стрес (ТЕС) є критичним фактором навколишнього середовища, який порушує фізіологічний та метаболічний баланс молочних корів, що призводить до зниження продуктивності, пригнічення імунітету та оксидативного стресу. Порода бурих швейцарських корів відома своєю відносно вищою термотолерантністю, проте її гематологічні та біохімічні реакції на гострий ТЕС залишаються маловивченими. Метою цього дослідження було оцінити вплив гострого теплового стресу на гематологічні та біохімічні параметри молочних корів породи бурі швейцарські корови, визначивши ключові фізіологічні адаптації та потенційні біомаркери для оцінки стресу. В експерименті взяли участь 16 корів породи бурі швейцарські корови під час другої лактації, розділених на групу теплового стресу (HYP, n = 8) та контрольну групу (CON, n = 8). Умови теплового стресу характеризувалися температурно-вологісним індексом (THI) 77,6 протягом п'яти послідовних днів. Гематологічні та біохімічні аналізи проводилися за допомогою автоматизованого гематологічного аналізатора та біохімічних аналізів для оцінки здатності до транспорту кисню, метаболічних адаптацій та імунних реакцій. Результати продемонстрували значні зміни ключових показників крові внаслідок гострого ТЕС. Концентрація гемоглобіну знизилася на 8,8% (P < 0,05), тоді як кількість тромбоцитів та рівень лейкоцитів знизилися на 30,2% та 25,1% відповідно (P < 0,05), що свідчить про гемопоетичні та імунні зміни. Біохімічні дані показали збільшення концентрації альбуміну на 21,8% (P < 0,05), а також підвищення рівня азоту сечовини в крові на 77,5% (P < 0,05), що свідчить про посилений катаболізм білка. Крім того, загальний рівень ліпопротеїнів збільшився на 56,3% (P < 0,05), а концентрація β-каротину зросла на 87,1% (P < 0,05), що відображає метаболічні зрушення та адаптацію до оксидативного стресу. Таким чином, гострий тепловий стрес викликає значні гематологічні та біохімічні зміни у корів бурої швейцарської породи, впливаючи на транспорт кисню, імунну функцію та регуляцію метаболізму. Результати дослідження підкреслюють фізіологічні компроміси, необхідні для терморегуляції, підкреслюючи необхідність цілеспрямованих харчових та екологічних стратегій для підвищення стійкості молочної худоби до теплового стресу. Необхідні подальші дослідження для вивчення довгострокової адаптації та розробки практичних підходів до пом'якшення наслідків.
Вплив гострого теплового стресу на гематологічні та біохімічні профілі корів бурої швейцарської породи
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: metabolic regulation; метаболічна регуляція; heat stress; тепловий стрес; dairy cows; молочні корови; blood parameters; показники крові; Brown Swiss; коричнева швейцарська порода